2019
DOI: 10.1186/s12896-019-0553-3
|View full text |Cite
|
Sign up to set email alerts
|

Structure-based engineering of heparinase I with improved specific activity for degrading heparin

Abstract: Background Heparinase I from Pedobacter heparinus (Ph-HepI), which specifically cleaves heparin and heparan sulfate, is one of the most extensively studied glycosaminoglycan lyases. Enzymatic degradation of heparin by heparin lyases not only largely facilitates heparin structural analysis but also showed great potential to produce low-molecular-weight heparin (LMWH) in an environmentally friendly way. However, industrial applications of Ph-HepI have been limited by their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…The superimposition of BcHep-I and BtHep-I ( Fig 5C) showed that BcHep-I has a similar steric structure with BtHep-I and both enzymes bind calcium ion with Trp, Asn, Asp, and Glu residues. The substrate-binding involved many direct and water-mediated hydrogen bonds between the sulfate groups and the basic side chains within the active site [36,37]. The critical residues in active pockets of the Hep-I were shown in Fig 5D. These residues including Gln15, Lys74, Arg76, Lys104, Arg149, Gln208, Tyr336, Tyr342, and Lys338 connected the heparin by forming hydrogen bonds.…”
Section: Plos Onementioning
confidence: 99%
“…The superimposition of BcHep-I and BtHep-I ( Fig 5C) showed that BcHep-I has a similar steric structure with BtHep-I and both enzymes bind calcium ion with Trp, Asn, Asp, and Glu residues. The substrate-binding involved many direct and water-mediated hydrogen bonds between the sulfate groups and the basic side chains within the active site [36,37]. The critical residues in active pockets of the Hep-I were shown in Fig 5D. These residues including Gln15, Lys74, Arg76, Lys104, Arg149, Gln208, Tyr336, Tyr342, and Lys338 connected the heparin by forming hydrogen bonds.…”
Section: Plos Onementioning
confidence: 99%
“…Enzyme activity at the optimum pH was defined as 100%, and the relative enzyme activity of HepI was determined. Enzyme activity was measured at 25,30,35,40,45,50, and 55℃ to determine the optimum reaction temperature. Enzyme activity at the optimum temperature was defined as 100%, and the relative enzyme activity of HepI was determined.…”
Section: Determination Of Enzyme Activity Enzymatic Properties Kineti...mentioning
confidence: 99%
“…The samples were successively mixed with the R1, R2, and R3 (buffers in the kit). The reaction was terminated by adding a citric acid solution; absorbance was measured at 405 nm [35].…”
Section: Potency Testing Of Enzymatic Digestion Productsmentioning
confidence: 99%
“…A sulfated glycosaminoglycan, heparin was named after its initial isolation from liver tissue a century ago [ 1 , 2 ]. It exists in the lung, vascular wall, intestinal mucosa, and so on.…”
Section: Introductionmentioning
confidence: 99%